Improving drug delivery technology for treating neurodegenerative diseases. (2nd July 2016) - Choonara, Yahya E.; Kumar, Pradeep; Modi, Girish; Pillay, Viness
ABSTRACT: Introduction : Neurodegenerative diseases (NDs) represent intricate challenges for efficient uptake and transport of drugs to the brain mainly due to the restrictive blood-brain barrier (BBB). NDs are characterized by the loss of neuronal subtypes as sporadic and/or familial and several mechanisms of neurodegeneration have been identified. Areas covered : This review attempts to recap, organize and concisely evaluate the advanced drug delivery systems designed for treating common NDs. It highlights key research gaps and opinionates on new neurotherapies to overcome the BBB as an addition to the current treatments of countering oxidative stress, inflammation and apoptotic mechanisms. Expert Opinion : Current treatments do not fully address the biological, drug and therapeutic factors faced. This has led to the development of vogue treatments such as nose-to-brain technologies, bio-engineered systems, fusion protein chaperones, stem cells, gene therapy, use of natural compounds, neuroprotectants and even vaccines. However, failure of these treatments is mainly due to the BBB and non-specific delivery in the brain. In order to increase neuroavailability various advanced drug delivery systems provide promising alternatives that are able to augment the treatment of Alzheimer's disease and Parkinson's disease. However, much work is still required in this field beyond the preclinical testing phase.